2011
DOI: 10.1093/annonc/mdq460
|View full text |Cite
|
Sign up to set email alerts
|

Double heterozygosity in the BRCA1 and BRCA2 genes in the Jewish population

Abstract: Background: The frequency and characteristics of disease in individuals who concomitantly harbor pathogenic mutations in both BRCA1 and BRCA2 genes are not established.Materials and methods: Data were collected from the database of Clalit Health Services National Familial Cancer Consultation Service. Probands referred to this clinical service and their family members are routinely tested for the three Jewish founder mutations (BRCA1:185delAG, 5382insC, BRCA2:6174delT). In addition, carriers identified in a pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 13 publications
2
46
0
1
Order By: Relevance
“…The most frequent mutations in BRCA1 gene were 509C [ A and 5615_5625del11insA, each of them was found 11 times, respectively. In BRCA2 gene, 7708C [ T was most frequently identified, which [18,21]. But there has been few reports regarding the prevalence among non-Ashkenazi carriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent mutations in BRCA1 gene were 509C [ A and 5615_5625del11insA, each of them was found 11 times, respectively. In BRCA2 gene, 7708C [ T was most frequently identified, which [18,21]. But there has been few reports regarding the prevalence among non-Ashkenazi carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies dealing with double heterozygosity for BRCA1 and BRCA2 mutations have been come from western countries, including Ashkenazi Jewish population [17][18][19][20][21]. But there has been few reports regarding double heterozygosity for the genes in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…The cloning of two major BC susceptibility genes, BRCA1 and BRCA2, in 1994 and 1995 (Futreal et al, 1994;Miki et al, 1994;Wooster et al, 1994; and the subsequent development of commercial genetic testing has brought hereditary cancer genetics into the public eye. BRCA1 mutations are uniformly more frequent than BRCA2 mutations (Malone et al, 2006;Hall et al, 2009;Kurian et al, 2010) with some exceptions (Nelson-Moseke et al, 2004) and a number of studies have reported an extremely rare case of familial BC with deleterious germline mutations in both BRCA1 and BRCA2 genes (double heterozygosity) (Lavie et al, 2011;Nomizu et al, 2012). The major role of BRCA1 appears to be DNA repair including homologous recombination and nucleotide excision repair (Roy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ashkenazi Jewish descent is the most important predictor for compound heterozygosity [2][3][4][5][6][7][8][9]. The likelihood of being a carrier of a common BRCA1 or BRCA2 founder mutation is as high as 1 in 40, and it is estimated that 0.3% of all breast cancer cases in the Ashkenazi Jewish population are compound heterozygotes [10,11]. However, the prevalence of these mutations in a non-Ashkenazi population is as low as 0.11% for BRCA1 and 0.12% for BRCA2 [12].…”
Section: Introductionmentioning
confidence: 99%